Integrated Science : worktext in science - Albarico, Joni M. (Lipa City, Batangas: United Eferza Academic Publications, Co., 2010)
"The Science Links (Revised Edition) is a program that provides the pupils the application of concepts, thus, preparing them to become effective problem solvers. It develops the pupils' deeper understanding of science concepts and leads them to Project-Based Learning (PBL) tasks that enhance design thinking. It uses the LINKS Instructional Design Model accompanied by the best instructional and assessment practices for effective learning process." --Back cover
Young Adult
Text in English
Keywords: Science -- Study and teaching -- Secondary education